Chemical element profiling in hair of bipolar disorder patients and healthy controls - Zannadeh, Hiba; Aas, Monica; Sampath, Vishnu Priya; Andreassen, Ole; Steen, Nils Eiel; Jørgensen, Kjetil Nordbø; Tirosh, Ofir; Lichtstein, David (Frontiers in Physiology, 2026)
Introduction Bipolar disorder (BD) is a severe psychiatric disorder characterized by shifting of mood patterns from manic to depressive episodes. The molecular mechanisms underlying BD have not been fully elucidated, and research into biomarkers is important for prevention and early intervention. The Na+, K+-ATPase is a metalloprotein that interacts with many chemical elements. It was demonstrated that the interactions of Na+, K+-ATPase with endogenous cardiac steroids is involved in BD. It was hypothesized that these interactions are mimicked by chemical elements which may participate in BD etiology. We have recently demonstrated that the concentration of Aluminum (Al), Boron (B), Cupper (Cu), Potassium (K), Magnesium (Mg) and Vanadium (V) were significantly lower in the pre-frontal cortex of individuals with BD compared with controls. We hypothesized that differences in the levels of chemical elements between BD and healthy controls would also be reflected in scalp hair.MethodsTo test this hypothesis, the levels of 25 chemical elements were determined by Inductively coupled plasma mass spectrometry (ICP-MS) in the scalp hair of 30 individuals with BD and 30 sex- and age-matched controls.ResultsWe found that the levels of Al, Cu, Nickel (Ni) and Thallium (Tl) are elevated in the hair of BD patients compared to controls. In addition, the concentrations of Ni levels in hair samples were correlated with the severity of the mental illness as quantified by the Global Assessment of Functioning Scale.ConclusionAlthough interpretations are tentative due to the limited sample size, our results suggest that changes in chemical elements may be involved either in the etiology of BD or altered due to the disease progression, which needs to be clarified further in larger independent samples.